Industrial Firms' Grand Strategy and Functional Importance: Moderating Effects of Technology and Uncertainty - Hitt, Michael A.; Ireland, R. Duane; Palia, K. A. (Academy of Management Journal, 1982)
The impact of four grand strategies on the relative importance of seven organizational functions and the moderating effects of type of production system and perceived environmental uncertainty were examined. The strategic importance of organizational functions was found to vary by grand strategy. Type of production system and perceived environmental uncertainty showed weak moderating effects.